Time series analysis on rate of malaria and typhoid fever: case study Nigeria (2003-2017) - Nwakuwa, Esther Promise (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management